The stress granule protein G3BP1 binds viral dsRNA and RIG-I to enhance interferon-β response - Kim, Susana Soo-Yeon (2019)
RIG-I senses viral RNA in the cytosol and initiates host innate immune response by triggering the production of type 1 interferon. A recent RNAi knockdown screen yielded close to hundred host genes whose products affected viral RNA-induced IFN-β production and highlighted the complexity of the antiviral response. The stress granule protein G3BP1, known to arrest mRNA translation, was identified as a regulator of RIG-I–induced IFN-β production. How G3BP1 functions in RIG-I signaling is not known, however. Here, we overexpress G3BP1 with RIG-I in HEK293T cells and found that G3BP1 significantly enhances RIG-I–induced ifn-b mRNA synthesis. More importantly, we demonstrate that G3BP1 binds RIG-I and that this interaction involves the C-terminal RGG domain of G3BP1. Confocal microscopy studies also show G3BP1 co-localization with RIG-I and with infecting vesicular stomatitis virus in Cos-7 cells. Interestingly, immunoprecipitation studies using biotin-labeled viral dsRNA or poly(I·C) and cell lysate–derived or in vitro translated G3BP1 indicated that G3BP1 could directly bind these substrates and again via its RGG domain. Computational modeling further revealed a juxtaposed interaction between G3BP1 RGG and RIG-I RNA-binding domains. Together, our data reveal G3BP1 as a critical component of RIG-I signaling and possibly acting as a co-sensor to promote RIG-I recognition of pathogenic RNA.